Evaluation of the Effect on Sexual Performance of a Nutraceutical Combination Containing Alpha Lipoic Acid, Vitis vinifera L. and Ginkgo biloba, Compared to Placebo, Avanafil or a Combination of Nutraceutical Plus Avanafil in Males With Type 2 Diabetes Mellitus With Erectile Dysfunction - Derosa, Giuseppe; D’Angelo, Angela; Preti, Paola Stefania; Maffioli, Pamela (Frontiers in Endocrinology, 2022)
Aim: to evaluate if therapy with a nutraceutical combination of alpha lipoic acid, Vitis vinifera L. and Ginkgo biloba (Blunorm forte®) can be helpful and be synergic with Avanafil. Methods: the trial included 123 males with type 2 diabetic mellitus and with erectile dysfunction (ED), aged ≥18 years. Patients were divided in four different arms: 1st arm: placebo during the three months of treatment and before sexual act; 2nd arm: placebo for 1 month, then placebo for two months and Avanafil: 1 tablet, 200 mg, 15-30 minutes before sexual act; 3rd arm: Blunorm forte: 1 tablet, 40 minutes before the meal (breakfast) during the three months and Avanafil: 1 tablet, 200 mg, 15-30 minutes before sexual act; 4th arm: Blunorm forte: 1 tablet, 40 minutes before the meal (breakfast and dinner) during the three months and placebo 15-30 minutes before sexual act. Results: a significant reduction of fasting plasma glucose, and homeostasis model assessment-insulin resistance index were recorded both in Avanafil + Blunorm forte and with Blunorm forte. Metalloproteinases-2, and -9 were reduced in the Avanafil + Blunorm forte group. High sensitivity-C-reactive protein was decreased by both Avanafil, and Avanafil + Blunorm forte group. No variations were recorded with the other treatments. The group treated with Blunorm forte and Avanafil reached a higher International Index of Erectile Function (IIEF) score after 3 months of therapy compared to baseline and placebo and compared to Avanafil and Blunorm forte taken alone. Conclusion: Blunorm forte® can be helpful and synergic with Avanafil in increasing sexual performance compared to placebo.